Analysis Implementation Analytical Hierarchy Process Method and Weighted Product for Ranking Internet Package Selection System - Abdi Pandu Kusuma (Universitas Muhammadiyah Sidoarjo, 2021)
The use of the internet is now with the increasing human need for information obtained using internet media. A decision support system (SPK) that is able to assist internet package users in determining the selection of internet packages and criteria can be used as a solution. This SPK implements the Analytical Hierarchy Process (AHP) and Weighted Product (WP) methods, the AHP method is used to determine the value of the weight criteria which is then used to calculate the WP method in determining the ranking of alternative internet packages. The criteria used in the AHP method include price, quota, signal quality, speed, and package type. The input data in the form of the weight value is calculated using the WP method to determine the best internet package. The results of the implementation of the AHP method were obtained on the criteria of price, quota, signal, speed, and package of 0.351; 0.279; 0.16; 0.14; and 0.07. The results of the implementation of the WP method based on the value of the weighting of the criteria from the results of processing the AHP method obtained Axis 1 GB data package as the selected internet package with a value of 0.256.